Preparation and physicochemical characterization of dioctyl sodium sulfosuccinate (aerosol OT) microemulsion for oral drug delivery - El-Laithy, Hanan M. (Springer-Verlag, 2003)
The performance of dioctyl sodium sulfosuccinate (aerosol OT) in the development of a pharmaceutically acceptable, stable, self-emulsifying water continuous microemulsion with high dilution efficiency was assessed. A pseudoternary microemulsion system was constructed using aerosol OT/medium-chain triglycerides with oleic acid/glycerol monooleate and water. The model microemulsion was characterized with regard to its electroconductive behavior, eosin sodium absorption, interfacial tension, and droplet size measurements after dilution with water. The percolation transition law, which makes it possible to determine the percolation threshold and to identify bicontinuous structures, was applied to the system. The interfacial tension changes associated with the microemulsion formation revealed ultralow values up to 30% oil at a surfactant/cosurfactant ratio of 3∶1. Moreover, the investigated particle size and polydispersity using photon correlation spectroscopy after dilution with excess of the continuous phase proved the efficiency of the microemulsion system as a drug carrier that ensures an infinitely dilutable, homogeneous, and thermodynamically stable system.